Impact of extended dual antiplatelet therapy on long‐term prognosis in patients with acute coronary syndrome complicated with anemia: A sub‐analysis of the real‐world OPT‐CAD study. Issue 2 (5th April 2021) - Zhao, Yu; Li, Jing; Ma, Sicong; Jiang, Zaixin; Li, Zhiguo; Wang, Xiaozeng; Han, Yaling; Li, Yi
Abstract: Objectives: To evaluate the impact of extended dual antiplatelet therapy (DAPT) beyond 12 months on long‐term prognosis in acute coronary syndrome (ACS) patients complicated with anemia undergoing percutaneous coronary intervention (PCI). Background: Anemia is frequent among ACS patients and is associated with increased risk of adverse clinical outcomes. Methods: A total of 6, 953 patients were enrolled from the Optimal anti Platelet Therapy for Chinese patients with Coronary Artery Disease (OPT‐CAD) study. A landmark analysis comparing extended DAPT versus single antiplatelet therapy (SAPT) at 12–24 months were performed in anemia patients without premature discontinuation of DAPT before 9 months and major clinical adverse events within 12 months. The primary outcome was major adverse cardiovascular and cerebrovascular events (MACCE), defined as a composite of all‐cause death, myocardial infarction, and stroke. Results: Patients with anemia ( n  = 1, 728) had higher rates of MACCE, all‐cause mortality, and BARC type 2, 3, 5 bleeding ( p  < .05) compared to those without anemia ( n  = 5, 225). Anemia patients received extended DAPT ( n  = 1, 010) were associated with a lower risk of stroke (0.3% vs. 1.8%; HR, 0.14; 95% CI, 0.03–0.71; p  = .018) compared to those received SAPT ( n  = 342). The rates of MACCE and all revascularization were lower in patients with extended DAPT, but the differences were not statistically significant. Risk of all‐cause mortality and bleeding were comparable between the two groups. Conclusions: Extended DAPT beyond 12 months may reduce the incidence of stroke without increasing the risk of bleeding in anemic ACS patients who tolerate 12‐month DAPT.